DELINEASI RESERVOIR SISTEM HIDROTERMAL GEDE-PANGRANGO BERDASARKAN DATA GEOKIMIA FLUIDA DAN STRUKTUR GEOLOGI - Iswahyudi, Sachrul
Gede-Pangrango volcanic hydrothermal system is a high terrain and temperature geothermal system. Study of remote sensing and analysis of geothermal fluid were carried on to delineate hydrothermal system associated with Gede Volcanoe. Analysis of lineament density and thermal anomalies (brightness temperatures) in Landsat image show areas with a high density of lineament with thermal anomalies (brightness temperatures), identified as a discharge area, and ones with high lineament density and low thermal anomalies as recharge area. Compilation with fluid geochemistry indicates that Gede volcanic hydrothermal system consists of 3 hydrothermal system, i.e. Gunung Pancar, Gunung Gede and Cikundul. Gunung Pancar hydrothermal system has reservoir temperature of 180oC and at 1000 m depth in Tertiary sedimen formation; the recharge area located at southeast area of the reservoir and the discharge manifestations are Gunung Pancar hotspring and Kawah Merah hotpool. Gunung Gede has reservoir of 290-300oC at 2000 m depth in Quartenary age volcanic rocks. Origin of geothermal fluids is meteoric water with minor magmatic fluid. The meteoric water of Gunung Gede infiltrates to the reservoir at northeast, barat and south areas of the reservoir. The hydrothermal fluids then appear at the surface as upflow at Gede Crater fumarole and outflowing to Green Apple hotspring. Cikundul hydrothermal system has reservoir temperature of 130-140oC and at 700 m depth in Quartenary age volcanic rocks; the recharge area located at south and northeast of the reservoir and the discharge ones are Cikundul hotsprings. All three reservoirs are separated by geological structures, where cold water infiltrates and acting as barrier within reservoirs.